2011
DOI: 10.1186/1750-1172-6-78
|View full text |Cite
|
Sign up to set email alerts
|

Anderson's disease/chylomicron retention disease in a Japanese patient with uniparental disomy 7 and a normal SAR1B gene protein coding sequence

Abstract: BackgroundAnderson's Disease (AD)/Chylomicron Retention Disease (CMRD) is a rare hereditary hypocholesterolemic disorder characterized by a malabsorption syndrome with steatorrhea, failure to thrive and the absence of chylomicrons and apolipoprotein B48 post-prandially. All patients studied to date exhibit a mutation in the SAR1B gene, which codes for an essential component of the vesicular coat protein complex II (COPII) necessary for endoplasmic reticulum to Golgi transport. We describe here a patient with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Sar1, a COPII component that initiates vesicle biogenesis, has two mammalian homologs: Sar1a and Sar1b (31). Several studies have shown that Sar1b is involved in lipoprotein trafficking and secretion because mutations in Sar1b lead to chylomicron retention disease (32)(33)(34)(35)(36). The definitive role of Sar1 in VLDL exit from the hepatic ER has been evident from our data and those of others (15,21).…”
supporting
confidence: 78%
“…Sar1, a COPII component that initiates vesicle biogenesis, has two mammalian homologs: Sar1a and Sar1b (31). Several studies have shown that Sar1b is involved in lipoprotein trafficking and secretion because mutations in Sar1b lead to chylomicron retention disease (32)(33)(34)(35)(36). The definitive role of Sar1 in VLDL exit from the hepatic ER has been evident from our data and those of others (15,21).…”
supporting
confidence: 78%
“…The meat quality of foreign sheep is higher than that of domestic Chinese sheep, and Gansu Alpine Merino [40], and are also superior to some non-domestic breeds of sheep [41].…”
Section: Discussionmentioning
confidence: 92%
“…Chylomicron retention disease (Anderson’s disease) [24] and abetalipoproteinemia [25, 26] are two examples of diseases where CM synthesis or secretion are inhibited and TAG accumulates in CLDs within enterocytes, ultimately resulting in fat malabsorption or steatorrhea due to enterocyte turnover. Pluronic L81 (PL81) is a surfactant that has been investigated because of its beneficial effects on reducing blood TAG and cholesterol levels.…”
Section: Dietary Fat Absorption - Overviewmentioning
confidence: 99%